Pengaruh Pemberian Penyuluhan Kesehatan tentang Kontrasepsi Efektif terhadap Partisipasi Ibu Post Partum dalam ber-KB - Remilda Armika Vianti; Sri Mumpuni Yuniarsih (Pena Medika Jurnal Kesehatan, 2010)
KB (family planning program) is one of the well-being service preventif most base and principal for woman. To optimalisasi family well-being benefit berencana, service must be provided for woman by unite and fulfil principal reproduction well-being service need and other, with responsively towards various woman reproduction life stage. enhanced and extension kb be one of [the] effort to increase painfulness number and mother death. This watchfulness aims to get well-being elucidation gift influence description about effective contraception towards mothers participation post partum in ber-kb. quantitative watchfulness with design quasy experiment that uses method case control that done in 80 mothers samples especially mother post partum primipara this use instrument sheet checklist. mother post partum that given has 40 and not given education has 40 people. mother that come along to participate in ber-kb after give education as big as 92,5% and doesn't come along to participate as big as 7,5% while group control that come along to participate in ber-kb after given elucidation as big as 27,5% and doesn't come along to participate as big as 72,5%. from analysis result is got there influence according to significant (have a meaning) between elucidation gift with mother participation ber-KB. The conclusion of this research is influence  mother participation ber-KB after health education.Keywords: Health education, KB, Participation